Challenges of e-learning development and implementation in remote Indonesia: educational development analysis - Khasanah; Rahanra, Nicodemus; Susanty, Lela (International research journal of management, IT and social sciences, 2021)
The main issue is the challenges of developing and implementing E-Learning in remote areas through analysis of education development during pandemic disturbances in many countries. We believe that if the challenges can be understood, how and why it will be easy to find solutions and become informed to policymakers. To understand the solution, we have collected data related to the above variables by electronic search in many scientific journals that examine the problems and challenges of implementing education during the COVID-19 disruption. Furthermore, the analysis effort involves a thoughtful data review, evaluation, and coding system so that we find understanding and draw conclusions with the consideration of answering the questions of this study with valid and reliable accuracy. This study relies on secondary data released between 2010 and 2021. We report the results in a descriptive qualitative design. So, the results include e-learning infrastructure and human educational resources, and students who are still having problems using technology and equipment. Learning Management System makes teachers and students confused in choosing which one is suitable for learning activities. Therefore, these results will bring benefits to the literature and other academic studies.